The value of CT head scans for patients from care homes presenting to the emergency department following a fall - Russell Taylor; Shams Duja (Clinical Medicine, 2025)
Introduction: Frail older patients from residential and nursing homes frequently attend the emergency department (ED) following falls, many of which are unwitnessed, making it difficult to determine whether a head injury was sustained. The current National Institute of Health and Care Excellence (NICE) guidelines for assessment of head injuries1 state that all patients taking anticoagulants should be considered for a computed tomography (CT) head scan within 8 h of the injury. This results in many care-home residents having repeated CT head scans because of recurrent attendances to ED with falls. It is uncertain as to whether this practice results in an increased pick-up rate of intracranial bleeds and, therefore, whether these scans are necessary for all patients on anticoagulants. Materials and Methods: All patients from residential and nursing homes who presented to ED in an acute hospital trust following a fall were identified between 1 December 2022 and 31 May 2023. Their medical notes were reviewed manually, and data were collected as to whether they were on anticoagulation before their fall, whether a CT head was performed, the result of the CT head and the outcome of any neurosurgical discussion if a bleed was identified. Data were also collected regarding hospital admission rates, length of stay, 28-day mortality and 28-day reattendance rates. Results and Discussion: 406 patients were identified who attended ED from care homes with a fall in during the 6-month period. Their demographics were as expected for an older cohort (59% women, 75% between the ages of 80 and 99). 37.4% of these patients were on anticoagulation (30.8% on a direct oral anticoagulant, 6.4% on warfarin and 0.2% on therapeutic enoxaparin). Of the cohort on anticoagulation, 69% of these patients had a CT head performed, compared with 30% in the cohort not anticoagulated (Fig 1). 4.8% of CT head scans performed on patients with anticoagulation showed a bleed, comparable to 3.9% of those performed on patients not anticoagulated (Fig 2). None of the bleeds in either cohorts required neurosurgical intervention. Admission rates were similar in both groups (61% admitted on anticoagulation, 58% admitted not on anticoagulation) Length of stay was comparable between the two groups. 28-day mortality rates were also similar (8.6% in anticoagulated group; 9.8% in group not anticoagulated). However, the readmission rates with a fall were significantly higher in the anticoagulated group (64.1% vs 46.3%). Conclusion: These results show that a significant proportion of our care-home residents presenting with falls are on anticoagulation (37%). Substantially more CT heads were performed in the anticoagulated cohort (69% vs 30%), with no significant difference in the pick-up rate of intracranial bleeds between the two cohorts (4.8% vs.3.9%). Therefore, we suggest that the routine undertaking of CT head scans on all patients with falls from care homes is not necessary and, instead, clinical judgement should be used to request scans for patients where there is clinical concern of a possible bleed. This practice would significantly reduce the number of CT head scans performed, and help to ease pressure on ED by increasing the speed of discharge.